The role of plant extracts in increasing vegetative growth and productivity in plants, biological control, and reducing environmental pollution - saad , Sabr; Adnan, Hala (University of Thi-Qar Journal of agricultural research, 2025)
The current study reviewed previous research using a range of plant extracts, including garlic, licorice, coconut milk, banana pulp, tomato juice, orange juice, dill oil, caraway, fenugreek, okra, jujube, and extracts from various weed plants such as wheatgrass, barley, mallow, and galangal, as well as volatile and fixed oils from cypress leaves, mint, eucalyptus, myrtle, cypress fruits, bitter orange, anise, date pits, soybeans, and others. The results showed significant differences between the various treatments. Some plant extracts contributed to increased vegetative and flowering growth and productivity compared to the control group. Furthermore, their addition to the nutrient medium in plant tissue culture stimulated the growth of the cultured plant part. Research also demonstrated that plant extracts can inhibit potato tuber germination. Studies and research have also shown the significant role of plant extracts in controlling insect pests, exhibiting pesticide effects against various insect species, including the southern cowpea beetle.